Impact of factor rotation methods on simulation composite indicators - Rukšėnaitė, Jurga (Mathematical Modelling and Analysis, 2011)
In this research one hypothesis about mathematical measure, which can be used as an additional tool for analysis and assessment Lithuania's economy tendencies, is verified. This additional measure has been constructed as a composite indicator (CI), involving indicators from social and economic fields. Simulated 45 different CIs have been obtained using several factor rotation methods. The analysis proved that standard mathematical methods may be used for composing CI, which give significant results analyzing Lithuania's economy state. Simulated CI during stable or growing periods have shown similar tendencies like GDP. Also our research proved that during crisis period different rotation methods may have influence on final results of CI.